Monitoring the pH Levels of Well Water in the Home Industri Sarung Goyor Village, Pemalang, Using IoT Technology and Inverse Distance Weight Method - Imam Ahmad Ashari; Purwono Purwono; Irfan Arfianto (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
The Sarung Goyor Home Industry business, located in Wanarejan Utara Village, Pemalang, has been running for several years. However, the use of residual textile dyes in the process of making goyor sarongs now poses a threat to the quality of well water in the area where residents live. This condition is a serious concern because some residents rely on water from the well for drinking, cooking, bathing, and washing. One of the impacts of this textile waste is abnormal water pH. The solution requires real-time monitoring of the pH of well water by utilizing Internet of Things (IoT) technology and pH sensors. In this solution, direct sampling using sensors is carried out at 3 monitoring points around the industrial area and processed to estimate the pH level of residents' well water. This monitoring system succeeded in showing that the average pH of well water was in a safe condition, namely 7.18, not much different from tests carried out with reference sensors, namely a pH range between 6.96 to 7.20. The findings show that in testing the assembled sensor, the IDW method has a measurable error rate with an RMSE of about 0.2629 and a MAPE of about 4.669%. When compared with the test results using a reference sensor, the RMSE value reaches around 0.4666 and the MAPE is around 6.553%.